'Paul Donning Mosaic Garb?': The Use of Deuteronomy 32 in Philippians 2:12-18 - Allen, David M. (European journal of theology, 2017)
Philippians 2:12-18 is unusual within the overall letter for its use of, or allusion to, Old Testament imagery. A common strand running through the unit is its appropriation of Deuteronomic imagery, and specifically of the Song of Moses and its immediate context. Paul uses the language and imagery of Deuteronomy 32, presenting a form of quasi-Mosaic farewell address, but reworked in the light of his confidence about the fate of the Philippians. Where Moses 'failed' due to the faithlessness of Israel at Meribah, Paul expects his audience to 'succeed', and he patterns his exhortation upon Moses' final words to Israel.